Sinergi Ekopedagogik dan Pedagogik Futuristik dalam Mengembangkan Kompetensi Sosial dan Ekologis Siswa Sekolah Dasar - Gina Garnika Dwinita; Dinie Anggraeni Dewi; Yusuf Tri Herlambang (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The global ecological crisis and the rapid advancement of technology demand a transformation in the paradigm of elementary education. This article aims to examine the synergy between ecopedagogy and futuristic pedagogy as a strategic approach to developing the social and ecological competencies of elementary school students. The study was conducted through a literature review using a critical thematic analysis approach of relevant, recent, and accredited scientific articles. The analysis reveals that ecopedagogy fosters critical awareness of social and environmental issues through reflective learning and transformative action, while futuristic pedagogy emphasizes digital literacy, technological integration, and future orientation to shape adaptive and visionary learners. The synergy of these approaches produces a contextual, inclusive, and sustainable learning model that strengthens critical thinking, collaboration, and environmental awareness. The conclusion of this study recommends the development of curricula and learning strategies that integrate sustainability values with 21st-century skills in order to shape a generation that is resilient both socially and ecologically.